2016
DOI: 10.1515/hukin-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Performance Effects of Repetition Specific Gluteal Activation Protocols on Acceleration in Male Rugby Union Players

Abstract: Warm-up protocols have the potential to cause an acute enhancement of dynamic sprinting performance. The purpose of this study was to evaluate the effects of three repetition specific gluteal activation warm-up protocols on acceleration performance in male rugby union players. Forty male academy rugby union players were randomly assigned to one of 4 groups (control, 5, 10 or 15 repetition gluteal activation group) and performed 10 m sprints at baseline and 30 s, 2, 4, 6 and 8 min after their specific intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…In contrast with some of the previous literature, [11][12][13] this study did not demonstrate any change in the performance outcome after activation warm-up. One reason for this may be that previous authors have been somewhat overeager to support the efficacy (and use) of gluteal activation warm-ups and have overstated the meaning of their results.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast with some of the previous literature, [11][12][13] this study did not demonstrate any change in the performance outcome after activation warm-up. One reason for this may be that previous authors have been somewhat overeager to support the efficacy (and use) of gluteal activation warm-ups and have overstated the meaning of their results.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Comyns and colleagues 12 reported that a gluteal warm-up can enhance force production based on changes in the ground reaction force–time curve, despite the fact that jump performance (height) was impaired for all of their post-warm-up jumps. The same group also suggested that a gluteal activation protocol can improve acceleration performance 13 but again this was based on a small, significant effect size (a difference in 10 m sprint time of 0.02 s; d≈0.2, p=0.021). What is particularly surprising in all of this previous literature is the focus on investigating whether the performance outcome is improved, especially when the clinical rationale for including gluteal activation exercises in an athlete’s programme is often more focused around improving movement quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations